The effectiveness of the communication methods used in e- learning during the Corona pandemic – A field study on students of Palestine University – - Abu Jaber, Amr Sabri (Journal of Humanities & Social Sciences, 2021)
Objective: The study aimed to identify the effectiveness of the communication methods used in e- learning from the point of view of the students themselves and the extent to which they achieve educational objectives through the electronic platform and its means and methods, to monitor the level of interaction of students with faculty through the communication methods applied in e- learning at the University of Palestine, and to explain the shortcomings of the communication methods applied in e- learning and its impact on students’ educational attainment. Methods: The study relied on the survey curriculum, under which the survey paper tool was used, an objective tool used to collect data from Palestinian students at the University of Palestine and the effectiveness of their use of communication methods in e- learning as an alternative to education, and its impact on educational attainment. The study was applied to a sample of (240) students from the University of Palestine with its various faculties and departments. Results: The communication methods applied in e- university education at the University of Palestine came from the point of view of the members of the study sample with a "medium" degree, and whatsapp was ranked first for its excellence as a means of discussion and exchange of work and in the second place "Yubinar" as it enables students to send educational files and duties and attach electronic lectures. Conclusion: The interaction of students with faculty through the communication methods applied in e- learning at the University of Palestine from the point of view of the members of the study sample received a "moderate" degree, and the communication methods used at the University of Palestine had the positive impression that they had enabled students to receive lectures, costs and exam dates first by the faculty, and that they urged them to complete these costs and complete the examinations. The shortcomings of the communication methods applied in e- education and its impact on students’ educational attainment came from the point of view of the study sample members to a "significant extent", due to "power outages, especially during examinations", "the difficulty of distinguishing between student levels under e- education". Study recommendations: Work to improve the quality of communication methods applied in e- learning and train students intensively on communication techniques and use them, especially students with deficiencies in this aspect, and "integrate social media, communication methods and strategies in addition to the various mobile applications employed in education.